Rural parents' perceptions of their involvement in their children's education :a study among the Sa'ban community within the Punang Kelapag region of Ulu Baram - Paulus, Balan. (Universiti Malaysia Sarawak, UNIMAS, 2008)
Expanding the involvement of parents in their children has been viewe d as an important strategy to advance the effectiveness and improve the quality of education. The ultimate objective of increasing the involvement of parents in children’s education is to expand the social and cognitive capabilities of children. Apparently , research carried out on parental involvement have indicated a distinct variation to occur mainly in the level of involvement and this variation seemed to be chiefly influenced by the socio - economic position and ethnic background of parents. Generally, pa rents from low socio - economic position and minority groups indicate low level of involvement in their children’s education because they are faced with various obstacles such as lack of time, lack of financial support, lack of knowledge and skills, do not k now how to become involved and underrepr esented. This study investigated the perceptions of Sa’ban parents, a rural community of the Punang Kelapang, towards their involvement in their children’s education. Twenty - four parents (twelve couples) with school - going children were selected and interviewed for this study. Qualitative analysis of the results indicated that the Sa’ban parents perceived the necessity of their involvement but their concern with making a living and lack of education prevented them from bringing their concerns about their children’s education to the teachers. Their involvement took the form of parenting, learning at home, communicating, volunteering, collaborating with the community and making decision. Results are discussed in relation to the patterns of involvement activities reported by the parents and implications for intervention in enhancing parents’ involvement process.